Analysis of a phased array antenna based on phase-shifters with ferroelectric varactors - Sengupta, L.; Kozyrev, A.B.; Osadchy, V.N.; Kosmin, D.M.; Bolihov, O.L.; Golovkov, A.A.; Kalinikos, D.A.; Pivovarov, I.Yu; Sugak, M.I.; Fedotov, A.N.; Vishnevetsky, A.S.; Zverev, A.K. (CriMiCo 2002 : 12th International Conference "Microwave & Telecommunication Technology" : conference proceedings, September 9-13, 2002, Sevastopol, Crimea, Ukraine, 2002)
Results of theoretical analysis and experiments for separate parts and elements of a flat multilayer microstrip phased array antenna based on phase-shifters with ferroelectric varactors are presented. Mutual coupling and crosspolarization phenomena between radiator elements of two-layer patch aperture have been theoretically and experimentally studied. Calculated and measured data on the phase-shifter parameters are presented.